Aplikasi Fungisida dan Pupuk Silika untuk Menekan Penyakit Bercak Daun Pyricularia zingiberi pada Jahe Merah - Sari, Marlina Puspita; Wahyuno, Dono; Hardiyanti, Siti; Manohara, Dyah (Jurnal Fitopatologi Indonesia, 2022)
Application of Fungicides and Silica Fertilization Suppress Pyricularia zingiberi Leaf Spot Disease on Red Ginger Pyricularia zingiberi is the dominant cause of leaf spot disease in Indonesia. Leaf spot disease control still relies on chemical fungicides. The combination of control techniques and the fungicide application timing must be determined to increase control effectiveness and reduce the negative impact of using chemical fungicides. This study aims to assess the combination of fungicide and silica fertilizer and the effective time for controlling leaf spot disease. The research was arranged in a split-split plot design, with silica fertilizer as the main plot, fungicide as a subplot, and the time of application as a subplot. Silica fertilizer (20 mL L-1) was applied at four weeks old red ginger, and then plants were inoculated with P. zingiberi at eight weeks of age. Fungicides were used according to the treatments (12, 14, and 16 weeks of age). There is no interaction between the three tested factors. The application of silica in the form of SiO2 had no significant effect on the severity and rate of disease progression. The application of silica increases the phenol content in red ginger plants. Botanical pesticides made from clove oil induce the synthesis of salicylic acid but are not significant in suppressing the rate of development of leaf spot disease. Mancozeb was more effective in suppressing the rate of development of leaf spot disease than other treatments. The recommended time for fungicide application is when the plants are 14–16 weeks old or when the symptoms of leaf spots begin to appear. Monitoring periodically is necessary.